Effect of sofosbuvir and velpatasvir therapy on clinical outcome in hepatitis C virus patients with decompensated cirrhosis. Issue 4 (22nd December 2022) - Tahata, Yuki; Sakamori, Ryotaro; Maesaka, Kazuki; Doi, Akira; Yamada, Ryoko; Kodama, Takahiro; Hikita, Hayato; Miyazaki, Masanori; Nozaki, Yasutoshi; Kaneko, Akira; Oshita, Masahide; Tanaka, Satoshi; et al.
Abstract: Aim: To determine the impact of direct‐acting antiviral therapy on the long‐term prognosis of decompensated cirrhotic patients. Methods: A total of 37 patients with hepatitis C virus‐induced decompensated cirrhosis treated with sofosbuvir and velpatasvir (SOF/VEL group) were prospectively enrolled. For historical control, 65 hepatitis C virus‐positive decompensated cirrhotic patients who did not receive direct‐acting antiviral therapy were included (control group). The incidence rates of hepatocellular carcinoma (HCC), decompensated events with hospitalization, and overall survival were compared between both groups. Results: A total of 41 patients experienced decompensated events during 15.0 months in the control group, and six patients during 21.6 months in the SOF/VEL group. The cumulative incidence rates of decompensated events after 2 years were significantly higher in the control group (53.1%) than in the SOF/VEL group (14.5%; p  < 0.001). A total of 27 patients died within 22.0 months in the control group, and three patients died within 25.6 months in the SOF/VEL group. The overall survival rates after 2 years were significantly lower in the control group (67.6%) than in the SOF/VEL group (91.3%; p  = 0.010). A total of 13 patients in the control group developed HCC during 15.8 months, and 10 patients during 17.3 months in the SOF/VEL group. The HCC incidence rates after 2 years were 20.3% and 29.6% in the control and SOF/VEL groups, respectively, with no significant difference ( p  = 0.327). Conclusions: SOF/VEL therapy may suppress the development of decompensated events and improve the prognosis in decompensated cirrhotic patients; however, the incidence of HCC remains prevalent in these patients irrespective of SOF/VEL therapy.